LANDSLIDE DISASTER MITIGATION IN RAHTAWU VILLAGE GEBOG KUDUS - Faikhotur Rohmah; Icha Khusnul Mawaddah; Dany Miftah M. Nur (International Journal of Multidisciplinary Reseach, 2025)
Natural disasters are uncontrolled natural events or occurrences that can cause serious damage to the environment, property, and human life. Natural disasters can occur due to various natural factors such as geology, weather, or atmospheric activity. Landslides are one of the natural disasters that often occur in Indonesia as a country with various geographical conditions and different regional topography. Landslides can be triggered by various factors, namely earthquakes, vegetation, and climate. The increase in groundwater levels causes the soil to become saturated, so that the shear strength of the soil decreases. Disaster mitigation is an effort made to reduce the risk of disasters, both before and after a disaster occurs. Disaster mitigation can be done through physical development or increasing public awareness. Disaster mitigation carried out includes spatial planning, development of disaster-resistant infrastructure, environmental monitoring, community outreach, and disaster preparedness. This study aims to examine landslide disaster mitigation and to determine the active involvement of the Rahtawu village community in landslide disaster mitigation. The qualitative method is descriptive in nature with data collection carried out through interviews, observations, and documentation to determine disaster mitigation efforts from the government and local communities.